Smart plugging and low-damage foam drilling fluid technology for CBM drilling. (23rd November 2022) - Li, Zhiyong; Zhou, Yu; Qu, Long; Zhang, Xufei
Once the drilling fluid filtrate invades along microfractures of coal reservoirs during the drilling process, it can cause notable wall instability. Foam spheres would infiltrate and move through the pores and into the fractures under drilling differential pressure between the wellbore and formation. As a result, microfoams deformed and the volume became larger to achieve plugging. In order to improve the foam foaming performance and stability during drilling, thereby enhancing the plugging effect, a new type of anionic Gemini surfactant, ZY-1, was designed and synthesised. Not only did ZY-1 reduce surface tension but also the half-life of foams produced was more than three times that of conventional foaming agents. Furthermore, contact angle recovery rate of cores and the desorption rate of drilling fluid reached 86% and 88.24%, respectively. And the plugging rate and gas permeability recovery value after pollution were both above 90% for the developed low-damage drilling fluid. [Received: October 24, 2021; Accepted: April 26, 2022]